The Lipid-Lowering Efficacy of a Nutraceutical Combination Including Leucoselect Phytosome, Red Yeast Rice, Policosanol and Folic Acid in Dyslipidaemia Patients: Real-World Insights - Vincenzo Russo; Nicola Napolitano; Antonia Ascrizzi; Silvia Leonardi; Filomena Pisacane; Pierpaolo Di Micco; Egidio Imbalzano; Ferdinando Carlo Sasso; Antonello D'Andrea; Alfredo Caturano; Alfredo Mauriello (MDPI AG, 2024)
Background: Cardiovascular disease is a global health concern and reducing plasma LDL-C levels is a major goal in cardiovascular prevention. Our study aimed to evaluate the effectiveness of a nutraceutical formulation including leucoselect® phytosome®, red yeast rice, policosanol and folic acid on LDL-c levels in patients at low cardiovascular risk with dyslipidemia. Materials and Methods: We prospectively enrolled all consecutive patients with dyslipidemia at low cardiovascular risk who were unresponsive to diet and physical activity. Clinical assessments and laboratory analyses, encompassing lipid profile, hepatic function, and CPK levels, were performed at baseline prior to initiating treatment and repeated at the 12-week mark following administration of the study nutraceutical. Results: Sixty (60) consecutive patients (mean age 48.02 ± 10.1 years; 60% male) were included. At the 12-week follow-up, a statistically significant reduction in Total Cholesterol (13.1%) and LDL-c serum level (20.4%) was observed. Hepatic and muscular function remain stable over the time. The adherence to therapy was 99% and the persistence was maximum. Conclusions: The nutraceutical formulation including leucoselect® phytosome® red yeast rice, policosanol and folic acid significantly reduced the LDL-c plasma levels, consistent with previous research showing that the bioactive component in red yeast rice-lovastatin-is effective in addressing problems with lipid metabolism. Importantly, it was safe and well-tolerated among patients with dyslipidemia in a real-world setting.